EXPERIMENTAL EVALUATION OF SOLAR DRYER FOR KOKAM FRUIT (Global Journal of Science Frontier Research, 2012)
Rotary solar dryer developed and evaluated for Kokam drying. Kokam fruits were selected as drying material. Time required reducing the moisture content upto 10 % as a safe storage for solar dryer was observed for ripen and unripe kokam fruits. Evaluation parameters were collection efficiency, system drying efficiency, pick-up efficiency, moisture ratio and drying rate. Maximum temperature inside the foldable solar dryer was 570C whereas maximum ambient temperature observed was 35.30C and solar irradiation was 600 W/m2.Humidity varies from 32.2% to 22.3% inside the solar dryer whereas outside humidity varies from 43.02% to 29.35%. Overall collection efficiency was found as 70.97 %. Maximum drying efficiency for salted ripen kokum was 9.88 per cent and unsalted salted ripen kokum was 7.66 percent.
Keywords: Collection efficiency; System drying efficiency; Pick-up efficiency; Moisture ratio; Drying rate